THE ROLE OF URBAN SUFISM OF SHALAWAT MUHAMMAD ASSEMBLY ON URBAN MIDDLE CLASS SOCIETY - Rubaidi Rubaidi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This article critically examines the role of Sufism in the process of social change in society,especially among urban societies that are symbolized by their middle class society. The subjectin this study is the Shalawat Muhammad Assembly under Mursyid Gus Kahar and his successor,Gus Mustakim. Although the assembly represents the urban sufism, but it has rooted fromclassical Sufism. In analyzing the role of this assembly in the process of social change in society,the theoretical framework of Cultural Brokers and Cultural Trendsetter of Geertz and Hirokosiare used as perspectives. The result simultaneously, consistently, and progressively shows thatSufism has a major contribution in any social change of societies to the value and ideology fromthe outside. The inherent value system in Sufism symbolized by the guru (murshid), is not just arole as a cultural broker as mentioned by the theory of Geertz. In fact, all gurus (mursyid) arewilling to change the value and ideology from the outside into a new system of traditions andcultures. This phenomenon resembles the cultural role of kyai in the Islamization of Indonesiain the past. It is the same like the theory of the cultural trendsetter of Hirokosi